Plan de negocio para la producción y comercialización de manteca de cacao en el mercado local y extranjero - Torres Baldeón, Edwin Oswaldo (2013)
In order to determine the feasibility of this project to create a business plan for the production and marketing of cocoa butter in the local and overseas market, we conducted a market survey, technical, organizational and financial support, the same as presented the following results: To develop the market study was conducted field research, it became known that the tastes and preferences of the target group (producers of cocoa, Local market and foreign market) it is composed of:...